FeCo-N-C catalyst, preparation method and application thereof, and method for degrading antibiotics
By developing FeCo-N-C catalyst to activate peracetic acid, the problem of poor removal of antibiotic pollutants in traditional water treatment methods is solved, and the effect of efficient degradation of antibiotics in a wide pH range is achieved, and good regeneration performance and environmental protection is achieved.
Patent Information
- Application Number
- CN202411696611.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-25
AI Technical Summary
Traditional water treatment methods have limited effect on removing antibiotic pollutants, and the reaction rate of peracetic acid is slow and corrosive at high concentrations, which limits its effect in practical applications.
A FeCo-N-C catalyst was developed to degrade antibiotics in water such as sulfamethoxazole by activating peracetic acid (PAA). This catalyst has excellent PAA activation performance, can maintain good degradation effect in a wide pH range, and can effectively degrade antibiotics even in complex water environments.
It significantly improves the activity of PAA, allowing it to degrade antibiotics in a short time, and is suitable for practical water treatment applications. The catalyst can maintain high degradation efficiency after multiple cycles, has good stability and renewability, reduces the cost of use, and the by-products produced after degradation are non-toxic and harmless, meeting environmental protection requirements.
Smart Images

Figure CN119565649A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water treatment, and in particular to a FeCo-NC catalyst, a preparation method and application thereof, and a method for degrading antibiotics. Background Art
[0002] Sulfamethoxazole is a common antibiotic widely used in medical and aquaculture industries. However, with the extensive use of antibiotics, antibiotic pollution has become one of the main threats to water pollution. Due to its difficult-to-degrade properties, sulfamethoxazole exists in the water environment for a long time, posing a potential threat to the ecological environment and human health.
[0003] Traditional water treatment methods have limited effects on the removal of antibiotic pollutants. In recent years, peracetic acid (PAA), as a highly efficient oxidant, has attracted widespread attention in the field of wastewater treatment. PAA has shown good results in degrading refractory organic pollutants, and the byproducts produced after degradation are relatively harmless. However, PAA has a slow reaction rate and is corrosive at high concentrations, which limits its effectiveness in practical applications. Therefore, the development of efficient catalytic materials to accelerate the activation of PAA has become a research hotspot. Summary of the invention
[0004] The present invention provides a FeCo-NC catalyst, a preparation method and application thereof, and a method for degrading sulfamethoxazole, aiming to degrade antibiotics such as sulfamethoxazole (SMX) in water by activating peracetic acid (PAA); the catalyst has excellent PAA activation performance, can maintain good degradation effect in a wide pH range, and can still efficiently degrade SMX even in a complex water environment (such as containing multiple anions and humic acid).
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a method for preparing a FeCo-NC catalyst, comprising the following steps:
[0007] Dissolving ferrous salt in water, and then adding polyvinyl pyrrolidone to obtain a mixed solution;
[0008] The aqueous solution of K3[Co(CN)6] is added to the mixed solution, reacted at 80-90°C, filtered, the solid was collected, dried, and calcined under an inert atmosphere to obtain a FeCo-NC catalyst.
[0009] Preferably, the calcination temperature is 700-850° C. and the calcination time is 1.5-2.5 h.
[0010] Preferably, K3[Co(CN)6] aqueous solution is added to the mixed solution, reacted at 80-90°C for 20-25h, filtered, the solid is collected, dried, and calcined under an inert atmosphere to obtain a FeCo-NC catalyst.
[0011] Preferably, the ferrous salt is FeCl2·4H2O, and the mass volume ratio of FeCl2·4H2O, polyvinyl pyrrolidone, water, and K3[Co(CN)6] aqueous solution is (0.03-0.04) g:(0.5-0.7) g:(20-25) mL:(20-25) mL.
[0012] Preferably, the inert atmosphere includes at least one of nitrogen, helium, argon and neon.
[0013] Preferably, the concentration of the K3[Co(CN)6] aqueous solution is 0.05-0.1 mol / L.
[0014] In a second aspect, the present invention further provides a FeCo-NC catalyst prepared by the preparation method.
[0015] In a third aspect, the present invention also provides a FeCo-NC catalyst prepared by the preparation method or use of the FeCo-NC catalyst in degrading antibiotics in water.
[0016] Preferably, the present invention also provides a method for degrading antibiotics, comprising the following steps:
[0017] The FeCo-NC catalyst prepared by the preparation method or the FeCo-NC catalyst is added to the wastewater containing antibiotics, and peracetic acid is added to the wastewater;
[0018] The FeCo-NC catalyst degrades antibiotics in wastewater by activating peracetic acid.
[0019] Preferably, in the step of adding the FeCo-NC catalyst to the wastewater containing antibiotics and simultaneously adding peracetic acid to the wastewater, the concentration of the FeCo-NC catalyst in the wastewater is 100 to 500 mg / L, the concentration of the peracetic acid in the wastewater is 50 to 200 μM, and the pH of the wastewater is 3 to 9;
[0020] The antibiotics include at least one of sulfamethoxazole, tetracycline, ciprofloxacin and quinolone.
[0021] The FeCo-NC catalyst, preparation method and application thereof, and method for degrading antibiotics of the present invention have the following beneficial effects compared with the prior art:
[0022] 1. The FeCo-NC catalyst of the present invention is a nitrogen-doped carbon-based composite material with good catalytic performance. Compared with traditional carbon nanotube catalysts, the FeCo-NC catalyst not only has excellent activity, but also can be easily recovered by an external magnetic field due to its unique magnetic properties, which reduces operating costs and improves its feasibility in industrial applications;
[0023] 2. The FeCo-NC catalyst of the present invention can significantly improve the activity of PAA, enabling it to degrade antibiotics such as sulfamethoxazole in a relatively short time, and is suitable for practical water treatment applications;
[0024] 3. The FeCo-NC catalyst of the present invention has a wide range of applications: the catalytic system exhibits good degradation effects in the range of pH 3 to 9, and can still maintain high degradation capabilities in the presence of complex water components such as anions and humic acid;
[0025] 4. The FeCo-NC catalyst of the present invention has good regeneration performance: after multiple cycles of use, the catalyst can still maintain a high degradation efficiency, has good stability and renewability, and reduces the cost of use;
[0026] 5. The FeCo-NC catalyst of the present invention is environmentally friendly and safe: the byproducts produced after the degradation of peracetic acid are water, acetic acid and carbon dioxide, which are non-toxic and harmless and meet environmental protection requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0028] Figure 1 is a scanning electron microscope (SEM) image of the FeCo-NC catalyst prepared in Example 1;
[0029] Figure 2 This is the EDS scan of the FeCo-NC catalyst prepared in Example 1;
[0030] Figures 3-4 is a high resolution transmission electron microscopy (HRTEM) image of the FeCo-NC catalyst prepared in Example 1;
[0031] Figure 5 The XRD patterns of the FeCo-NC catalyst prepared in Example 1 before the reaction and the FeCo-NC catalyst recovered after the reaction according to the method in Example 2;
[0032] Figure 6 is the Raman spectrum of the FeCo-NC catalyst prepared in Example 1;
[0033] Figure 7 The X-ray photoelectron spectroscopy (XPS) spectra of the FeCo-NC catalyst prepared in Example 1 before the reaction and the FeCo-NC catalyst recovered after the reaction according to the method in Example 2;
[0034] Figure 8 is the specific surface area and pore size distribution of the FeCo-NC catalyst prepared in Example 1;
[0035] Fig. 9 The effects of wastewater pH value, peracetic acid concentration in wastewater, and FeCo-NC catalyst concentration on the degradation of sulfamethoxazole;
[0036] Fig.10 For different anions Cl - 、SO4 2- 、NO 3- , HCO 3- Effects on the degradation of sulfamethoxazole;
[0037] Fig.11 The effect of humic acid (HA) on the degradation of sulfamethoxazole;
[0038] Fig.12 These are the experimental results of recycling the FeCo-NC catalyst in Example 1 for 1 to 4 times under the optimal experimental conditions. DETAILED DESCRIPTION
[0039] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.
[0041] The present invention provides a method for preparing a FeCo-NC catalyst, comprising the following steps:
[0042] S1, dissolving ferrous salt in water, and then adding polyvinyl pyrrolidone to obtain a mixed solution;
[0043] S2. Add K3[Co(CN)6] aqueous solution to the mixed solution, react at 80-90°C, filter, collect the solid, dry it, and calcine it under an inert atmosphere to obtain a FeCo-NC catalyst.
[0044] In some embodiments, the calcination temperature is 700-850° C. and the calcination time is 1.5-2.5 h.
[0045] In some embodiments, K3[Co(CN)6] aqueous solution is added to the mixed solution, reacted at 80-90°C for 20-25h, filtered, the solid was collected, dried, and calcined under an inert atmosphere to obtain a FeCo-NC catalyst.
[0046] In some embodiments, the ferrous salt is FeSO4, FeCl2, Fe(NO3)2, etc. Preferably, the ferrous salt is FeCl2·4H2O. The mass volume ratio of FeCl2·4H2O, polyvinyl pyrrolidone, water, and K3[Co(CN)6] aqueous solution is (0.03~0.04) g:(0.5~0.7) g:(20~25) mL:(20~25) mL.
[0047] In some embodiments, the concentration of the K3[Co(CN)6] aqueous solution is 0.05-0.1 mol / L, preferably 0.05 mol / L.
[0048] In some embodiments, the inert atmosphere includes at least one of nitrogen, helium, argon, and neon.
[0049] The FeCo-NC catalyst of the present invention is a nitrogen-doped carbon-based composite material with good catalytic performance. Compared with traditional carbon nanotube catalysts, the FeCo-NC catalyst not only has excellent activity, but also can be easily recovered by an external magnetic field due to its unique magnetic properties, reducing operating costs and improving its feasibility in industrial applications.
[0050] Based on the same inventive concept, the present invention also provides a FeCo-NC catalyst, which is prepared by the above-mentioned preparation method.
[0051] Based on the same inventive concept, the present invention also provides a FeCo-NC catalyst prepared by the above preparation method or use of the above FeCo-NC catalyst in degrading antibiotics such as sulfamethoxazole in water.
[0052] The FeCo-NC catalyst of the present invention degrades antibiotics such as sulfamethoxazole (SMX) in water by activating peracetic acid (PAA). The catalyst has excellent PAA activation performance, can maintain good degradation effect in a wide pH range, and can still efficiently degrade SMX even in complex water environments (such as those containing multiple anions and humic acid). Experimental verification shows that the FeCo-NC catalyst of the present invention can increase the degradation rate of SMX to 91.5% within 90 minutes under the conditions of 25°C, pH 7.0, catalyst dosage of 0.5g / L, and initial PAA concentration of 100μM. In addition, after four cycles of use, the degradation efficiency of the catalyst remains above 70%, showing good regeneration ability and stability.
[0053] Based on the same inventive concept, the present invention also provides a method for degrading antibiotics, comprising the following steps:
[0054] The FeCo-NC catalyst prepared by the above preparation method is added into the wastewater containing antibiotics, and peracetic acid is added into the wastewater at the same time;
[0055] FeCo-NC catalyst degrades antibiotics such as sulfamethoxazole in wastewater by activating peracetic acid.
[0056] In some embodiments, in the step of adding FeCo-NC catalyst to wastewater containing antibiotics and simultaneously adding peracetic acid to the wastewater, the concentration of FeCo-NC catalyst in the wastewater is 100-500 mg / L, the concentration of peracetic acid in the wastewater is 50-200 μM, and the pH of the wastewater is 3-9.
[0057] In some embodiments, the antibiotics include at least one of sulfamethoxazole, tetracycline, ciprofloxacin, quinolone, and the like.
[0058] Specifically, in the above embodiments, the pH value of the wastewater is adjusted by adding H2SO4 or NaOH to the wastewater, the specific reaction temperature is room temperature (25°C), the time is 5 to 90 minutes, and the concentration of antibiotics such as sulfamethoxazole in the wastewater after the reaction is determined by LC-16 high performance liquid chromatography (HPLC).
[0059] The FeCo-NC catalyst of the present invention can significantly improve the activity of PAA, enabling it to degrade antibiotics such as sulfamethoxazole in a relatively short time, and is suitable for practical water treatment applications;
[0060] The FeCo-NC catalyst of the present invention has a wide application range: the catalytic system shows good degradation effect in the range of pH 3 to 9, and can still maintain high degradation ability in the presence of complex water components such as anions and humic acid;
[0061] The FeCo-NC catalyst of the present invention has good regeneration performance: after being used for multiple cycles, the catalyst can still maintain a high degradation efficiency, has good stability and renewability, and reduces the use cost.
[0062] The FeCo-NC catalyst of the present invention is environmentally friendly and safe: byproducts generated after degradation of peracetic acid are water, acetic acid and carbon dioxide, which are non-toxic and harmless and meet environmental protection requirements.
[0063] The following further illustrates the FeCo-NC catalyst of the present application and its preparation method and application, and the method for degrading antibiotics with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0064] Example 1
[0065] The present invention provides a method for preparing a FeCo-NC catalyst, comprising the following steps:
[0066] S1. Dissolve 0.0357 g of FeCl2·4H2O in 20 mL of ultrapure water, and add 0.6 g of polyvinylpyrrolidone (PVP) to obtain a mixed solution;
[0067] S2. Add 20 mL of 0.05 mol / L K3[Co(CN)6] (potassium cobalt cyanide, purchased from MacLean Reagent Company) aqueous solution to the mixed solution at a rate of 0.8 mL / min, and react vigorously in a water bath at 85°C for 20 hours; after the reaction is completed, filter the supernatant, collect the solid and wash it three times with deionized water, and then dry it at 60°C overnight, and finally calcine the solid product in a tubular furnace in a nitrogen atmosphere at 800°C for 2 hours to obtain a FeCo-NC catalyst.
[0068] Example 2
[0069] This embodiment provides a method for degrading sulfamethoxazole, comprising the following steps:
[0070] S1. Prepare 100 mL of wastewater containing 10 μM sulfamethoxazole, and adjust the pH value of the wastewater to 3-9 by adding H2SO4 or NaOH to the wastewater;
[0071] S2, adding the FeCo-NC catalyst prepared in Example 1 to the wastewater containing sulfamethoxazole in S1, and adding peracetic acid to the wastewater at room temperature (25° C.) for 5 to 90 minutes;
[0072] The concentration of FeCo-NC catalyst in the wastewater is 100-500 mg / L, and the concentration of peracetic acid in the wastewater is 50-200 μM;
[0073] After the reaction was completed, the concentration of sulfamethoxazole in the wastewater after the reaction was determined using LC-16 high performance liquid chromatography (HPLC).
[0074] Catalyst characterization
[0075] Figure 1 is a scanning electron microscope (SEM) image of the FeCo-NC catalyst prepared in Example 1.
[0076] Figure 2 This is the EDS surface scan of the FeCo-NC catalyst prepared in Example 1.
[0077] Figures 3-4 This is a high-resolution transmission electron microscopy (HRTEM) image of the FeCo-NC catalyst prepared in Example 1.
[0078] from Figures 1 to 4 It can be seen that the FeCo-NC catalyst prepared in the present invention has a spherical structure, a smooth surface, uniform distribution of elements and corresponding lattice crystal planes.
[0079] The XRD patterns of the FeCo-NC catalyst prepared in Example 1 before the reaction and the FeCo-NC catalyst recovered after the reaction according to the method in Example 2 were tested. The results are as follows: Figure 5 The specific reaction conditions are as follows: the initial sulfamethoxazole concentration in the wastewater is 10 μM, the pH value of the wastewater is 7, the reaction temperature is 25°C, the reaction time is 90 min, the concentration of the FeCo-NC catalyst in the wastewater is 500 mg / L, and the concentration of the peracetic acid in the wastewater is 100 μM.
[0080] from Figure 5 It can be seen that the structure of the FeCo-NC catalyst has not changed before and after the reaction, which shows the structural stability of the catalyst. The main crystal planes are all there. The diffraction peak at 23° belongs to the (002) crystal plane of graphite carbon (PDF#49-1721); the diffraction peaks at 44.5°, 64.5°, 82.2° and 99.1° belong to the (110), (200), (211) and (220) crystal planes of FeCo alloy, respectively (PDF#44-1433).
[0081] Figure 6 is the Raman spectrum of the FeCo-NC catalyst prepared in Example 1; Figure 6 The existence of sp2 and sp3 carbon networks in the catalyst material is demonstrated. The D-peak and G-peak are both Raman characteristic peaks of C atomic crystals, at 1300 cm -1 and 1580cm -1 Nearby, the D peak represents the defect of the C atom lattice, and the G peak represents the in-plane stretching vibration of the sp2 hybridization of the C atom. I(D) / I(G) is the intensity ratio of the D peak and the G peak, where I represents intensity. The I(D) / I(G) of the catalyst is 1.17.
[0082] The X-ray photoelectron spectroscopy (XPS) spectra of the FeCo-NC catalyst prepared in Example 1 before the reaction and the FeCo-NC catalyst recovered after the reaction according to the method in Example 2 were tested. The results are as follows: Figure 7 As shown; among them, Figure 7 Here, Fresh means before the reaction, Used means after the reaction, and the specific reaction conditions are: the initial sulfamethoxazole concentration in the wastewater is 10 μM, the pH value of the wastewater is 7, the reaction temperature is normal (25°C), the reaction time is 90 min, the concentration of FeCo-NC catalyst in the wastewater is 500 mg / L, and the concentration of peracetic acid in the wastewater is 100 μM.
[0083] from Figure 7It can be seen that the FeCo-NC catalyst contains four elements, Fe, Co, N, and C, before and after the reaction. The N 1s spectrum is divided into four peaks at 398.7, 399.6, 400.6, and 402.1 eV, which are attributed to pyridinic N, pyridinic N, graphitic N, and oxidized N, respectively; the high-resolution Co 2p spectrum is divided into two parts, Co 2p3 / 2 and Co2p1 / 2 spin orbits. In the Co 2p3 / 2 range, the typical peaks observed at 779.6, 781.2, 783.2, and 786.8 eV correspond to Co 0 、Co 3+ 、Co 2+ In the Co2p1 / 2 spectrum, the peaks centered at 796.7 and 798.4 eV correspond to Co 2+ and Co 3+ In addition, the Co 2p spectrum peak at 803.5 eV is attributed to the satellite peak. The high-resolution Fe2p spectrum is fitted to six peaks, including the two parts of the spin orbits of Fe 2p3 / 2 and Fe 2p1 / 2. The two peaks at 720.3 eV are satellite peaks in FeCo@NC, while the two pairs of peaks at 711.1 / 723.7 and 713.5 / 726.3 eV are Fe 2+ and Fe 3+ The XPS results of the FeCo-NC catalyst after the reaction were similar to this, with only the proportions of N, Fe, Co and C species changing.
[0084] Figure 8 Specific surface area and pore size distribution of the FeCo-NC catalyst prepared in Example 1 (measured by the Brenner-Emmett-Teller (BET) method).
[0085] Figure 8 According to the N2 adsorption-desorption isotherm, the BET specific surface area of the catalyst was calculated to be 73 m 2 / g, and the presence of mesopores plays a vital role in improving the catalytic activity by facilitating the mass transfer between substrates and oxidants.
[0086] According to the method in Example 2, the effects of the pH value of the wastewater, the concentration of peracetic acid in the wastewater, and the concentration of the FeCo-NC catalyst on the degradation of sulfamethoxazole were studied respectively. The results are as follows: Fig. 9 shown.
[0087] Specifically, Fig. 9 In (a), the pH value of the wastewater during the reaction ranged from 3 to 9 (pH 3, 5, 7, and 9, respectively), and the other conditions were fixed as follows: the initial sulfamethoxazole concentration in the wastewater was 10 μM, the concentration of the FeCo-NC catalyst in the wastewater was 500 mg / L, and the concentration of peracetic acid in the wastewater was 100 μM;
[0088] Fig. 9 In (b), the concentration of peracetic acid during the reaction was 0-200 μM (0 μM, 50 μM, 100 μM, 200 μM, respectively, 0 μM means no PAA), and the other conditions were fixed as follows: the initial sulfamethoxazole concentration in the wastewater was 10 μM, the pH value of the wastewater was 7, and the concentration of the FeCo-NC catalyst in the wastewater was 500 mg / L;
[0089] Fig. 9 In (c), the concentration of FeCo-NC catalyst in the wastewater during the reaction was 0-500 mg / L (0 mg / L, 100 mg / L, 200 mg / L, 500 mg / L, respectively, 0 mg / L means no catalyst), and the other conditions were fixed as follows: the initial sulfamethoxazole concentration in the wastewater was 10 μM, the pH value of the wastewater was 7, and the concentration of peracetic acid in the wastewater was 100 μM.
[0090] Fig. 9 In (a) to (c), C is the concentration of sulfamethoxazole (SMX) in the wastewater at time t, and C0 is the concentration of sulfamethoxazole (SMX) in the wastewater at time 0 (i.e., the initial time).
[0091] from Fig. 9 It can be seen that pH has little effect on the degradation rate of SMX, that is, the catalytic PAA technology can operate in a wide pH range; the degradation rate of SMX gradually increases with the increase of catalyst dosage and PAA concentration.
[0092] After comprehensively considering the cost and treatment efficiency, the optimal reaction conditions are: temperature 25°C, initial wastewater pH value 7.0, FeCo-NC catalyst dosage 0.5 g / L, and initial peracetic acid (PAA) concentration of 100 μM; under this condition, the degradation rate of 10 μM SMX in 90 minutes is 75%.
[0093] According to the method in Example 2, different anions Cl - 、SO4 2- 、NO 3- , HCO 3- , on the degradation of sulfamethoxazole, the results are as follows Fig.10 Specifically, Cl - 、SO4 2- 、NO 3- , HCO 3- Add in the form of sodium salt, the specific method is:
[0094] S1, prepare 100 mL of wastewater containing 10 μM sulfamethoxazole, and adjust the pH value of the wastewater to 7;
[0095] S2, adding the FeCo-NC catalyst prepared in Example 1 to the wastewater containing sulfamethoxazole in S1, and adding peracetic acid to the wastewater, and adding Cl - (added in the form of NaCl), at room temperature (25°C) for 5 to 90 minutes;
[0096] The concentration of FeCo-NC catalyst in the wastewater was 500 mg / L, the concentration of peracetic acid in the wastewater was 100 μM, and the concentration of Cl in the wastewater was - The concentration is 0-5mM (the concentrations are 0mM, 0.05mM, 0.5mM, 5mM, 0mM means no Cl - );
[0097] After the reaction was completed, the concentration of sulfamethoxazole in the wastewater after the reaction was determined using LC-16 high performance liquid chromatography (HPLC).
[0098] SO4 2- 、NO 3- , HCO 3- The experimental method for the effect on the degradation of sulfamethoxazole is the same as above, except that Na2SO4, NaNO3, and NaHCO3 are used instead of NaCl, respectively.
[0099] Fig.10 In the equation, C is the concentration of sulfamethoxazole (SMX) in the wastewater at time t, and C0 is the concentration of sulfamethoxazole (SMX) in the wastewater at time 0 (i.e., the initial time).
[0100] from Fig.10 It can be seen that Cl - and 5mM SO4 2- The presence of has a slight promoting effect on the degradation of SMX, while NO 3- The presence of 0.05 mM and 0.5 mM HCO had no effect on the degradation of SMX. 3- There is a significant inhibitory effect on the degradation of SMX, which shows that this technology can cope with the influence of conventional ions.
[0101] According to the method in Example 2, the effect of humic acid (HA) on the degradation of sulfamethoxazole was studied. The results are as follows: Fig.11 The specific method is as follows:
[0102] S1, prepare 100 mL of wastewater containing 10 μM sulfamethoxazole, and adjust the pH value of the wastewater to 7;
[0103] S2, adding the FeCo-NC catalyst prepared in Example 1 to the wastewater containing sulfamethoxazole in S1, and adding peracetic acid to the wastewater, and adding humic acid (HA) to the wastewater at room temperature (25° C.) for 5 to 90 minutes;
[0104] The concentration of FeCo-NC catalyst in the wastewater is 500 mg / L, the concentration of peracetic acid in the wastewater is 100 μM, and the concentration of humic acid (HA) in the wastewater is 0-30 mg / L (the concentrations are 0 mg / L, 1 mg / L, 5 mg / L, 10 mg / L, and 30 mg / L, respectively, and 0 mg / L means no humic acid (HA);
[0105] After the reaction was completed, the concentration of sulfamethoxazole in the wastewater after the reaction was determined using LC-16 high performance liquid chromatography (HPLC).
[0106] Fig.11 In the equation, C is the concentration of sulfamethoxazole (SMX) in the wastewater at time t, and C0 is the concentration of sulfamethoxazole (SMX) in the wastewater at time 0 (i.e., the initial time).
[0107] from Fig.11 It can be seen that the presence of humic acid inhibits the degradation of SMX, and the more HA is added, the more obvious the inhibition rate is. However, when the addition amount reaches more than 10 mg / L, the inhibitory effect of HA does not increase with the increase of HA concentration.
[0108] Fig.12 The experimental results are as follows: the FeCo-NC catalyst in Example 1 was recycled 1 to 4 times according to the method in Example 2 under the optimal experimental conditions; wherein the optimal conditions are: temperature 25°C, initial wastewater pH value 7.0, FeCo-NC catalyst dosage 0.5 g / L, and initial peracetic acid (PAA) concentration 100 μM.
[0109] Fig.12 In the equation, C is the concentration of sulfamethoxazole (SMX) in the wastewater at time t, and C0 is the concentration of sulfamethoxazole (SMX) in the wastewater at time 0 (i.e., the initial time).
[0110] from Fig.12 It can be seen that the FeCo-NC catalyst has stable performance towards SMX degradation after multiple cycles.
[0111] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a FeCo-NC catalyst, characterized in that: The following steps are involved: Dissolving ferrous salt in water, and then adding polyvinyl pyrrolidone to obtain a mixed solution; The aqueous solution of K3[Co(CN)6] is added to the mixed solution, reacted at 80-90°C, filtered, the solid was collected, dried, and calcined under an inert atmosphere to obtain a FeCo-NC catalyst.
2. The method for preparing the FeCo-NC catalyst according to claim 1, characterized in that: The calcination temperature is 700-850°C and the time is 1.5-2.5h.
3. The method for preparing the FeCo-NC catalyst according to claim 1, characterized in that: The aqueous solution of K3[Co(CN)6] was added to the mixed solution, and the mixture was reacted at 80-90°C for 20-25h. The solid was collected by filtration and dried, and then calcined under an inert atmosphere to obtain a FeCo-NC catalyst.
4. The method for preparing the FeCo-NC catalyst according to claim 1, characterized in that: The ferrous salt is FeCl2·4H2O, and the mass volume ratio of FeCl2·4H2O, polyvinyl pyrrolidone, water, and K3[Co(CN)6] aqueous solution is (0.03-0.04) g:(0.5-0.7) g:(20-25) mL:(20-25) mL.
5. The method for preparing the FeCo-NC catalyst according to claim 1, characterized in that: The inert atmosphere includes at least one of nitrogen, helium, argon and neon.
6. The method for preparing the FeCo-NC catalyst according to claim 1, characterized in that: The concentration of the K3[Co(CN)6] aqueous solution is 0.05-0.1 mol / L.
7. A FeCo-NC catalyst, characterized in that The preparation is obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the FeCo-NC catalyst prepared by the preparation method according to any one of claims 1 to 6 or the FeCo-NC catalyst according to claim 7 in degrading antibiotics in water.
9. A method for degrading antibiotics, characterized in that: The following steps are involved: Adding the FeCo-NC catalyst prepared by the preparation method of any one of claims 1 to 6 or the FeCo-NC catalyst of claim 7 to wastewater containing antibiotics, and simultaneously adding peracetic acid to the wastewater; The FeCo-NC catalyst degrades antibiotics in wastewater by activating peracetic acid.
10. The method for degrading antibiotics according to claim 9, characterized in that: In the step of adding the FeCo-NC catalyst to the wastewater containing antibiotics and simultaneously adding peracetic acid to the wastewater, the concentration of the FeCo-NC catalyst in the wastewater is 100 to 500 mg / L, the concentration of the peracetic acid in the wastewater is 50 to 200 μM, and the pH of the wastewater is 3 to 9; The antibiotics include at least one of sulfamethoxazole, tetracycline, ciprofloxacin and quinolone.
Citation Information
Patent Citations
Porous Fe3Co7@C nanosphere and application in catalytic degradation of organic pollutants
CN106824195A
Method for degrading antibiotics in water by activating peracetic acid through zero-valent metal
CN112723518A
Method for degrading organic pollutants by activating peroxymonosulfate with environment-interference-resistant Fe-coated N-CNs composite catalytic material
CN115677010A
Catalyst for rapidly degrading tetracycline hydrochloride wastewater by thermally activating peracetic acid as well as preparation method and application method of catalyst
CN116673032A
Preparation method of iron monatomic catalyst for generating singlet oxygen by activating persulfate and application of iron monatomic catalyst in degradation of new pollutants in water body
CN116832810A